2004
DOI: 10.1111/j.1399-0012.2004.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in stable renal transplant patients in Norway: morbidity and mortality during a 5‐yr follow‐up

Abstract: Thus, IHD was the major cause of death late after renal Tx, and a major ischemic heart event was predicted by baseline congestive heart failure, diabetes, age, hypertension, and hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 26 publications
2
72
2
4
Order By: Relevance
“…ANOVA or Kruskal-Wallis test was used to compare means for continuous variables, with 2 for categorical variables. To analyze whether PA is associated with mortality, we first performed a Kaplan-Meier analyses with a log-rank test.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA or Kruskal-Wallis test was used to compare means for continuous variables, with 2 for categorical variables. To analyze whether PA is associated with mortality, we first performed a Kaplan-Meier analyses with a log-rank test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The incidence and prevalence of cardiovascular disease (CVD) are estimated to be four to six times higher in renal transplant recipients (RTRs) than in the general population (1,2). Classical CVD risk factors such as dyslipidemia, hypertension, and obesity, which commonly coexist as the metabolic syndrome (MS), contribute to this excess in CVD (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Key Words: cardiovascular events Ⅲ mortality Ⅲ pulse wave velocity Ⅲ augmentation pressure Ⅲ augmentation index Ⅲ transplantation Ⅲ kidney A lthough the survival advantage offered by successful renal transplantation 1 in large part can be attributed to a long-term reduction of the cardiovascular (CV) disease progression and mortality, 2 the annual risk of CV death still remains Ϸ50-fold higher than in the general population. 3 Nevertheless, CV death rates in transplanted patients are reduced by approximately 75% compared with wait-listed patients remaining on dialysis. 4 This decrease in CV risk by partial restoration of kidney function can be offset by the emergence or worsening of other risk factors due to transplant-specific causes, such as acute rejection, infection, or side effects of immunosuppressive drugs, including newonset diabetes after transplantation (tacrolimus, steroids), dyslipidemia (calcineurin inhibitors, mammalian target of rapamycin inhibitors), and anemia (mammalian target of rapamycin inhibitors).…”
mentioning
confidence: 99%
“…Several observational studies showed that diabetes mellitus, left ventricular hypertrophia, age over 50 years, more than 1 year on dialysis, tobacco abuse, hypertension, left ventricular ejection fraction < 40%, and dyslipidemia were independent risk predictors of CVD and cardiac mortality in kidney transplant candidates. [15][16][17][18] The European Society of Cardiology guidelines on noncardiac surgery recommend that imaging stress testing may be considered in patients with 1 or 2 clinical risk factors and poor functional capacity (< 4 metabolic equivalents) before high-risk and intermediate-risk surgery with a class IIb recommendation and level of evidence C. 6 They identified the risk factors of ischemic heart disease (angina pectoris and/or previous myocardial infarction), heart failure, stroke or transient ischemic attack, and renal dysfunction (serum creatinine > 2 mg/dL or a creatinine clearance of < 60 mL/min/1.73 m 2 ) for perioperative cardiac events. Similarly, the 2012 American Heart Association/American College of Cardiology consensus statement recommended imaging stress tests on the evaluation and management of cardiac disease in kidney and liver transplant candidates with no active cardiac conditions on the basis of the presence of multiple coronary artery disease risk factors regardless of functional status (class IIb, with level of evidence C).…”
Section: Discussionmentioning
confidence: 99%